Contribution of mining in terms of canon and other royalties in Peru - Moscoso-Paucarchuco, Ketty M. (2021)
The present research aims to analyze the contribution of mining in terms of canon and other royalties, as well as the effectiveness of the distribution and execution of these resources. In this study, collection rates were observed, measured and analyzed in monetary terms; the characteristics of the data were determined through their collection; The inductive-deductive method was used specifically to general. The documentary review was based on the examination of the economic transfers to the different regions for mining canon and royalties, and the analysis of official data from transparency pages of various executing entities. As a conclusion, it is determined that the mining tax regime presents certain weaknesses, due to the existence of informal mining that does not provide fees or royalties, the unequal distribution of the budget, and finally the ineffective execution of investment projects financed with these resources, which do not They fulfill the public purpose, which is the reduction of poverty, mainly.